ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA DAN FASILITAS TERHADAP KEPUASAN PELANGGAN HOTEL PONDOK TINGAL DI KABUPATEN MAGELANG - Wibisono, Aryo Prasetyo (Diponegoro Journal of Management, 2015)
Currently the hotel business competition is very tight, so that the manager of the hotel should be able to provide the best service so that customers are satisfied. Customer satisfaction is the difference between expectations and perceived performance or services. Hotel Pondok Tingal, Jl. Balaputra Dewa 32, Borobudor, Magelang is a hotel that offers many advantages such as a more modern karaoke (computer use). However, the price offered at the hotel is more expensive than in other places, so the impact on the Pondok Tingal visitors in recent years. Based on the data, the Pondok Tingal visitors in 2013 decreased on average 4 person/month with a tendency in the past 4 months has decreased. A decrease is caused by many factors, one of which is a low customer satisfaction. In this study the factors that affect customer satisfaction is analyzed through service quality, price and facility. The purpose of this study was to analyze the impact of service quality, price and facilities on customer satisfaction Hotel Pondok Tingal in MagelangThe population in this study is the customer Hotel Pondok Tingal, Jl . Balaputra Dewa 32, Borobudor, in Magelang. The sample in this study was 100 customers. The sampling technique in this study conducted by purposive sampling technique. Data type is primary. Methods of data collection using the questionnaire . The analysis technique used is multiple regressionThe results of the analysis using SPSS showed that : Service quality affect on customer satisfaction. Competitive price affect on customer satisfaction. Facility effect on customer satisfaction